1980
DOI: 10.1080/0270271800010307
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Orientation for Reading Researchers

Abstract: This article examines the strengths and weaknesses of quantitative versus qualitative research methods in reading. While, until recently, the field of reading accounted for relatively few qualitative studies, the authors present ideas and methods that point the way for efforts in this direction. They conclude that the situation is changing, and because of recent trends at the Center for the Study of Reading qualitative designs in reading research may finally compete actively with quantitative measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The ability to segment words into phonemes is a predictor of spelling achievement (National Institute of Child Health and Human Development, 2000). Students need to know the names of the letters of the alphabet and need to recognize that those letters have direct associations to the sounds, which is known as the alphabetic principle (Vacca et al, 2006); this leads to phonological awareness and understanding that phonemes can be related to graphemes.…”
mentioning
confidence: 99%
“…The ability to segment words into phonemes is a predictor of spelling achievement (National Institute of Child Health and Human Development, 2000). Students need to know the names of the letters of the alphabet and need to recognize that those letters have direct associations to the sounds, which is known as the alphabetic principle (Vacca et al, 2006); this leads to phonological awareness and understanding that phonemes can be related to graphemes.…”
mentioning
confidence: 99%
“…To overcome the language barrier and to help students become more academically successful, it is essential for teachers to learn about the students’ respective cultures and the languages that the students speak for the purpose of assessing and planning for the best way to teach culturally and linguistically diverse students (Fitzgerald & Graves, 2004/2005; Young & Hadaway, 2006). Vacca et al (2015) noted that pre-service teachers should know that cultural diversity exists when students’ families, homes, cultures, socioeconomic statuses, and other societal differences appear differently from the dominant population of the school. According to Vacca et al (2015), the language that the student feels most comfortable using is referred to as linguistic diversity; however, this language may not be the predominant language of the school.…”
Section: Importance Of Recognizing Culture and Linguistics In Educational Settingsmentioning
confidence: 99%
“…Vacca et al (2015) noted that pre-service teachers should know that cultural diversity exists when students’ families, homes, cultures, socioeconomic statuses, and other societal differences appear differently from the dominant population of the school. According to Vacca et al (2015), the language that the student feels most comfortable using is referred to as linguistic diversity; however, this language may not be the predominant language of the school.…”
Section: Importance Of Recognizing Culture and Linguistics In Educational Settingsmentioning
confidence: 99%
“…Although reading research still tends to be dominated by quantitative designs, several researchers (Alexander, 1982;Carey, 1980;Vacca & Vacca, 1980) have recommended qualitative methodologies as appropriate alternatives. Alexander (1982) noted that qualitative methods may be more suitable than quantitative methods in the investigation of dynamic and complex phenomena such as reading, especially if one is interested in cognitive or socio-cultural aspects of reading.…”
mentioning
confidence: 98%
“…Carey (1980) stated that qualitative methodologies are appropriate for exploring the complex interrelationships operating within reading, as these methods help researchers explore the dynamic nature of reader-text-context interactions without dissecting the process into isolated bits for separate examination. Vacca and Vacca (1980) suggested that qualitative methods enable us to learn more about the process of reading by allowing us to examine natural interactions operating among variables in real reading situations.…”
mentioning
confidence: 99%